Walk in my combat boots [compact disc, unabridged] : true stories from America's bravest warriors - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Hachette Audio, 2021)
A powerful collection of never-before-told war stories crafted from hundreds of interviews by James Patterson and First Sergeant US Army (Ret.) Matt Eversmann.